Experiences of Emergency Surgical Treatment for a COVID-19 Patient with Severe Traumatic Brain Injury at a Regional Trauma Center: A Case Report - Jung-Ho Yun (Journal of Trauma and Injury)
Various medical scenarios have arisen with the prolonged coronavirus disease 2019 (COVID-19) pandemic. In particular, the increasing number of asymptomatic COVID-19 patients has prompted reports of emergency surgical experiences with these patients at regional trauma centers. In this report, we describe an example. A 25-year-old male was admitted to the emergency room after a traffic accident. The patient presented with stuporous mentality, and his vital signs were in the normal range. Lacerations were observed in the left eyebrow area and preauricular area, with hemotympanum in the right ear. Brain computed tomography showed a contusional hemorrhage in the right frontal area and an epidural hematoma in the right temporal area with a compound, comminuted fracture and depressed skull bone. Surgical treatment was planned, and the patient was intubated to prepare for surgery. A blood transfusion was prepared, and a central venous catheter was secured. The initial COVID-19 test administered upon presentation to the emergency room had a positive result, and a confirmatory polymerase chain reaction (PCR) test was administered. The PCR test confirmed a positive result. Emergency surgical treatment was performed because the patient’s consciousness gradually deteriorated. The risk of infection was high due to the open and unclean wounds in the skull and brain. We prepared and divided the COVID-19 surgical team, including the patient’s transportation team, anesthesia team, and surgical preparation team, for successful surgery without any transmission or morbidity. The patient recovered consciousness after the operation, received close monitoring, and did not show any deterioration due to COVID-19.